Prognostic Value of Androgen Receptor Splice Variant 7 in the Treatment of Metastatic Castration-Resistant Prostate Cancer: A Systematic Review and Meta-Analysis - Wang, Jiaxin; Zhang, Yucong; Wei, Chao; Gao, Xintao; Yuan, Penghui; Gan, Jiahua; Li, Rui; Liu, Zhuo; Wang, Tao; Wang, Shaogang; Liu, Jihong; Liu, Xiaming (Frontiers in Oncology, 2020)
Background: The prognostic value of androgen receptor splice variant 7 (AR-V7) for the treatment response of metastatic castration-resistant prostate cancer (mCRPC) remains unclear. In this study, we aimed to synthesize relevant studies that assessed the prognostic value of AR-V7 status for the treatment response of mCRPC patients treated with androgen receptor signalling inhibitors (ARSis) and chemotherapy. Methods: We searched the PubMed, Embase, and MEDLINE databases by using the keywords AR-V7 and prostate cancer to identify relevant studies published before 25 September 2019. The main outcomes were prostate-specific antigen (PSA) response, progression-free survival (PFS) and overall survival (OS). Pooled odds ratios (ORs) and hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated using a random effects model. The quality of the included studies was assessed using the Newcastle-Ottawa Quality Assessment Scale. Results: A total of 1,545 patients from 21 studies were included. For the mCRPC patients treated with ARSis, AR-V7-positive patients had a lower PSA response rate (OR 6.01, 95% CI 2.88-12.51; P < 0.001) , shorter PFS (HR 2.56, 95% CI 1.80-3.64; P < 0.001) and shorter OS (HR 4.28, 95% CI 2.92-6.27; P < 0.001) than AR-V7-negative patients. Although AR-V7-positive patients treated with chemotherapy also had a lower PSA response rate (OR 2.23, 95% CI 1.38-3.62; P = 0.001) and shorter OS than AR-V7-negative patients (HR 1.60, 95% CI 1.02-2.53; P = 0.043), there was no significant difference in PFS (HR 1.05, 95% CI 0.74-1.49; P = 0.796) between these groups. Furthermore, AR-V7-positive patients receiving ARSis had a shorter median OS than those receiving chemotherapy (HR 3.50, 95% CI 1.98-6.20; P < 0.001); There was no significant difference among AR-V7-negative patients (HR 1.30, 95% CI 0.64-2.62; P = 0.47). Conclusions: AR-V7 is a potential biomarker of treatment resistance in mCRPC patients. AR-V7-positive mCRPC patients had poorer treatment outcomes than AR-V7-nagetive patients when treated with ARSis. AR-V7-positive patients have better outcomes when treated with taxane than ARSis. Furthermore, the ability of AR-V7 status to predict treatment outcomes varies from different detection methods. The detection of AR-V7 before treatment is important for the selection of treatment modalities for mCRPC patients.